Refactoring Databases Evolutionary Database Design - Ambler, Scott W. 1966-; Sadalage, Pramod J. (Addison Wesley Professional, 2006)
Annotation
Includes bibliographical references and index
Keywords: Database design; Computer software -- Development; Evolutionary programming (Computer science); Database Management; Computers; Database Management; General; Engineering & Applied Sciences; Computer Science; Computer software; Development; Bases de données; Conception; Logiciels; Développement; Programmation évolutive; Datenbankentwurf; Engenharia de programas; Métodos ágeis; Banco de dados